2016
DOI: 10.1007/s11916-016-0580-x
|View full text |Cite
|
Sign up to set email alerts
|

Basilar Invagination, Basilar Impression, and Platybasia: Clinical and Imaging Aspects

Abstract: The congenital and acquired deformities of the craniovertebral junction (CVJ), such as basilar invagination, basilar impression, or platybasia, can present in the form of slowly progressive or acute neurologic deterioration. In many cases, an insidious headache is the only symptom and can be a diagnostic challenge for the neurologist. Proper imaging studies as well as recognizing often associated neurologic or systemic conditions are required for early diagnosis and effective therapy. In the current report, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 28 publications
0
50
0
Order By: Relevance
“…We used the previously described methods to measure posterior fossa structures. 9,[19][20][21][22][23][24][25] Details in e-methods (links.lww. com/NXG/A252).…”
Section: Measurementsmentioning
confidence: 99%
“…We used the previously described methods to measure posterior fossa structures. 9,[19][20][21][22][23][24][25] Details in e-methods (links.lww. com/NXG/A252).…”
Section: Measurementsmentioning
confidence: 99%
“…(35) Similarly, in our cohort BI likely develops secondary to undermineralized, weak bone in the cervical spine and skull base affected by FD. CM1 commonly occurs in association with BI, (13) in which malposition of the odontoid process causes refractory downward displacement of the cerebellar tonsils with or without decreased PCFV. (13,35,36) In this study, FD/MAS subjects with CM1 demonstrated a significant increase in odontoid position relative to Chamberlain's line, and 30% met criteria for BI, implicating cranial settling as a causal mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…CM1 commonly occurs in association with BI, (13) in which malposition of the odontoid process causes refractory downward displacement of the cerebellar tonsils with or without decreased PCFV. (13,35,36) In this study, FD/MAS subjects with CM1 demonstrated a significant increase in odontoid position relative to Chamberlain's line, and 30% met criteria for BI, implicating cranial settling as a causal mechanism. Boogaard angle was also increased in both the CM1 and BI groups, consistent with platybasia, or skull base flattening.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations